Fertility awareness and attitudes towards parenthood among Danish university college students - Sørensen, Nina Olsén (Reprod Health, 2016)
BACKGROUND: Postponing parenthood has steadily increased during the past decades in Western countries. This trend has affected the size of families in the direction of fewer children born per couple. In addition, higher maternal age is associated with an increased risk of pregnancy-related complications such as prematurity and foetal death, while higher paternal age increases the risk of miscarriage and affects time-to-pregnancy. Hence, understanding the circumstances and reflections that influence the decision is greatly needed and little is known about potential gender difference influencing the choice. The aim was to investigate attitudes towards parenthood, intentions for childbirth and knowledge about fertility issues among men and women. METHODS: We conducted a cross-sectional study based on a validated 49-item questionnaire among students, who attended selected mandatory lectures at a Danish university college in February to April 2016. The participation rate was 99%, and 517 completed the questionnaire. RESULTS: Though the majority of all participants wished to have children in the future (>86%), there was significant difference between the genders (p = 0.002). Women rated having children to be more important than men did (p < 0.001), while men rated higher the likelihood of abstaining from having children if faced with infertility (p = 0.003). Knowledge about fertility issues was similar between genders including poor knowledge about the age-related decline in female fertility. While women found it more important to have children before being ‘too old’ (p = 0.04), still more than 40% of all respondents intended to have their last child after the age of 35 years. For both genders the most important prerequisite for parenthood was having a partner to share responsibility with. Perceived or experienced life changes related to parenthood were generally positive such as personal development. CONCLUSION: The majority of respondents wished to have children, but many desired to have these after the biological decline in female fertility. The moderate knowledge level among both genders uncovered in this study is of concern. Future research should address the potential link between fertility knowledge and planning of parenthood. We may benefit from intervention studies examining the effect of routine preconception care.